A Case of Sigmoid Colon Cancer with Bladder Fistula Treated by Laparoscopic Radical Resection - Murotani, Masatoshi; Hirose, Hajime; Yoshioka, Shinichi; Mokutani, Yukako; Takeda, Masashi; Tamura, Shigeyuki; Sasaki, Yo (Gan to kagaku ryoho, 2022)
The patient was a woman in her 70 s. Computed tomography(CT)showed a sigmoid colon tumor invading the uterus and ovaries, and a fistula to the bladder. The patient was scheduled to receive neoadjuvant chemotherapy(NAC), but while waiting for treatment, generalized peritonitis due to perforation of the tumor was observed, and a laparoscopic transverse colostomy was performed. After NAC with CAPOX and FOLFIRI plus panitumumab, the tumor was found to have shrunk, and a laparoscopic posterior pelvic exenteration was performed. The bladder including the fistula was partially resected, and the tumor, uterus, and right ovary were resected in combination as R0, besides the ureter and remaining bladder could be preserved. The postoperative course was uneventful, and the patient is alive without recurrence to date. In this article, we report a case of a patient with sigmoid colon cancer with a bladder fistula who underwent laparoscopic surgery after NAC, and bladder function could be preserved, with some discussion of the literature.